High Performance Vector Control of 3-Phase IM Drives under Open-Phase Fault Based on EKF for Rotor Flux Estimation - Mohammad Jannati; Tole Sutikno; Nik Rumzi Nik Idris; Mohd Junaidi Abdul Aziz (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper proposes a novel flux observer based on Extended Kalman Filter (EKF) for high performance vector control of 3-phase Induction Motor (IM) drives under stator winding open-phase fault. The presented flux estimation combines the Indirect Rotor Field-Oriented Control (IRFOC) method. The rotor flux is obtained from two modified EKF with two different stator currents (forward and backward stator currents). The proposed technique can significantly reduce the DC-offset problem on the pure integrator associated with the basic IRFOC method. The Matlab simulation results confirm the validity of the proposed strategy.